Correlation between Sequential Organ Failure Assessment (SOFA) Score with Right Ventricular Systolic Function and Left Ventricular Filling Pressure in Sepsis Patients - Anindia Wardhani; M.Arif Nugroho; M.Fauziar Ahnaf; Johan Arifin; Tri Nur Kristina (Eduvest - Journal of Universal Studies, 2025)
This research aimed to evaluate the relationship of sepsis severity assessed using SOFA scores with RV systolic function and LVFP. Methods: This cross-sectional observational study involved 25 dr. Kariadi General Hospitals septic patients without cardiac disease. The SOFA score as a study subject was calculated up to a maximum of 3 times per patient parallel to the RV function examination.  Echocardiographic RV function parameter we used Tricuspid Annular Plane Systolic Excursion (TAPSE), Right Ventricle Fractional Area Change (RV-FAC), Right Ventricle Free Wall Strain (RV-FWS), Right Ventricle-Pulmonary Artery (RV-PA) coupling, and LVFP using the Nagueh formula and ASE/EACVI 2016 criteria. Correlation tests were conducted between SOFA scores with TAPSE, RV-FAC, RV-FWS, RV-PA coupling, and LVFP. Results: There were 56 samples of SOFA scores and echocardiography. There was a significant correlation between SOFA scores and TAPSE (r = -0.44, p = 0.001), RV-FAC (r = -0.54, p = <0.001), RV-FWS (r = -0.52, p = <0.001), RV-PA coupling (r = -0.32, p = 0.014). No significant correlation was found between SOFA and LVFP scores with Nagueh (r = 0.11, p = 0.42) and the 2016 ASE/EACVI criteria (r= -022, p= 0.09). RV-FWS can detect RV dysfunction earlier than other parameters. Conclusion: SOFA score is associated with RV function but not with LVFP. Echocardiography in septic patients can be considered to detect early RV dysfunction.